Teaching and learning in a competence‐based curriculum: the case of four secondary schools in England. Issue 3 (1st September 2013) - Byrne, Jenny; Downey, Christopher; Souza, Ana
Abstract : This article focuses on four case study schools that have adopted innovative competence‐based curriculum (CBC) projects in Year 7 for a variety of educational and social reasons. The article discusses the issues and challenges posed by the CBC for teachers in the daily life of the classroom. Philosophical ideas about the purpose of education vary because they are driven by ideological positions. Consequently the nature and structure of the curriculum influenced by the stance adopted inevitably affects approaches to teaching and learning. It is contended that changes to the curricula in the case study schools have revealed tensions between traditional approaches to teaching and learning with 'strong' classification and framing and the new, more progressive approaches with 'weak' classification and framing. These tensions impact on teachers' identities and this can make effective classroom practice problematic. The article concludes that managing the tensions between traditional and more progressive pedagogies is worthwhile as this will enable students to become more fully integrated, and successful participatory members of twenty‐first‐century society rather than simply reproducing the socio‐economic status quo, or the requirements of current dominant educational discourse in England.